2022
DOI: 10.1556/063.2021.00103
|View full text |Cite
|
Sign up to set email alerts
|

Driving employee-driven innovation through workplace learning: The story of Singapore SMEs

Abstract: This study is part of a larger research study that seeks to understand how employee-driven innovation (EDI) is initiated, enacted and sustained in small and medium enterprises (SMEs) in Singapore. To date, most of the EDI studies are conducted in the Nordic context where management, employees and public authorities work closely with each other. In more hierarchical societies, such as those in Asia, employees may be given less discretion in exercising initiative to improve work processes and conditions. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The engagement of employees and the burning commitment of enthusiastic individuals may make it last a while (more on that below), but a long-lasting realisation of an organisation's full innovation capacity requires organisational conditions that provide an expansive learning environment (cf. Evans & Waite, 2010;Fuller & Unwin, 2004;Tan & Sim, 2022). This result corroborates the results of previous scholars who have shown that expansive learning environments are needed to achieve better impact of investments in learning and EDI (Halvarsson Lundkvist & Gustavsson, 2017;Tan & Sim, 2022), and that workplaces with restrictive learning environments that invest in formal education programs do not reap the full benefits or long-term effects of their investments (Evans & Waite, 2010).…”
Section: The Importance Of An Expansive Learning Environmentsupporting
confidence: 87%
See 4 more Smart Citations
“…The engagement of employees and the burning commitment of enthusiastic individuals may make it last a while (more on that below), but a long-lasting realisation of an organisation's full innovation capacity requires organisational conditions that provide an expansive learning environment (cf. Evans & Waite, 2010;Fuller & Unwin, 2004;Tan & Sim, 2022). This result corroborates the results of previous scholars who have shown that expansive learning environments are needed to achieve better impact of investments in learning and EDI (Halvarsson Lundkvist & Gustavsson, 2017;Tan & Sim, 2022), and that workplaces with restrictive learning environments that invest in formal education programs do not reap the full benefits or long-term effects of their investments (Evans & Waite, 2010).…”
Section: The Importance Of An Expansive Learning Environmentsupporting
confidence: 87%
“…Employees represent enormous untapped potential; both because they are so numerous and because they work closely with citizens or end users of services or processes. Thus, they possess a wide range of context-dependent and experience-based knowledge that has been shown to be valuable in innovation work (Tan & Sim, 2022). By involving employees in innovation as part of their everyday work, the organisation may also become more internally malleable and responsive as new workplace goals emerge or demands from citizens or employees change (Billett, 2012).…”
Section: Employees-an Untapped Resourcementioning
confidence: 99%
See 3 more Smart Citations